(untitled) (Dhaka University Law Journal, 2025)
Land-based sources of marine pollution pose one of the most serious threats to the marine environment of Bangladesh. While the Bay of Bengal under Bangladesh’s territory provides the whole country with numerous opportunities and hope for a sustainable future, increased marine pollution from land-based sources is making those benefits run dry. This article explores the legal standards set by Bangladesh with a particular focus on the land-based activities polluting the marine environment. It discovers that the national legal and policy framework on environmental protection addresses the issue of marine pollution from land- based activities (MPLBA) step-by-step. However, those ambitious initiatives sadly fall short of holistic implementation measures. The paper finally identifies how the existing national, regional and international legal framework can best be applied to combat marine pollution from land-based activities in Bangladesh. Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 139-165